Study on the bilinear softening mode and fracture parameters of concrete in low temperature environments. (15th April 2019) - Hu, Shaowei; Fan, Bing
Highlights: Carry out the fracture experiment of concrete in low-temperature environment. Determine the bilinear softening curve using the inverse analysis. Find the influence of temperature on the softening curve and fracture parameters. Validation the correctness of softening curves based on the double-K fracture model. Abstract: The mode and fracture parameters of concrete at different temperature levels (20 °C, 0 °C, −20 °C, and −40 °C) were investigated using three-point bending fracture experiment in a low-temperature fracture test system. The three-point bending beams with the same sizes, 750 mm × 150 mm × 70 mm, were divided into two groups according to age: 28 days and 120 days. The bilinear softening parameters for each beam were determined using the inverse analysis; then, the fracture energy G F and characteristic length l ch were determined by the calculated softening curve. In addition, the fracture toughness including the initial fracture toughness K Ic ini, unstable fracture toughness K Ic un and cohesive toughness K Ic c were also analyzed. The experimental and calculation results show that the softening curve shape and fracture parameters of the concrete change significantly when the temperature decreases. Finally, the double-K fracture model was used to verify the validity of the bilinear softening curve calculated in this paper.